2022
DOI: 10.3390/ijerph19074266
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Neighborhood Characteristics among U.S. Children with Secondhand and Thirdhand Tobacco Smoke Exposure

Abstract: (1) Background: Home tobacco smoke exposure (TSE) and negative neighborhood characteristics adversely affect children’s overall health. The objective was to examine the associations of child TSE status and neighborhood characteristics among U.S. school-aged children. (2) Methods: We conducted a secondary analysis of the 2018–2019 National Survey of Children’s Health (NSCH) data including 17,300 U.S. children ages 6–11 years old. We categorized children’s home TSE status into: (a) no TSE: child did not live wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The overall thirdhand smoke exposure prevalence for young people in this survey is relatively higher than in other research. A study from the United States showed that among a sample of 17300 children, 2278 were exposed to thirdhand smoke, resulting in a thirdhand smoke exposure prevalence of 13.2% 23 . The MPOWER tobacco control strategy proposed by the World Health Organization in 2008 provides important references and guidance for China's implementation and promotion of smoke-free policies in public places 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The overall thirdhand smoke exposure prevalence for young people in this survey is relatively higher than in other research. A study from the United States showed that among a sample of 17300 children, 2278 were exposed to thirdhand smoke, resulting in a thirdhand smoke exposure prevalence of 13.2% 23 . The MPOWER tobacco control strategy proposed by the World Health Organization in 2008 provides important references and guidance for China's implementation and promotion of smoke-free policies in public places 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with past research [2,4], we also found that children with TSE were at increased risk to live in poverty. Families with low-incomes are more likely to live in lower quality homes in which lack of heat or air conditioning and increased litter and other negative elements create fertile conditions for mold and pests and other environmental hazards which adversely affect children's health [3,5,12]. Specifically, mold and damp home environments are present in approximately 18.7 million low-income homes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no safe level of tobacco smoke exposure (TSE) for children [1], almost one-in-four are exposed to tobacco smoke in their homes [2]. TSE rates are even higher in children who live in poverty, rented homes, and in neighborhoods in which there is litter, lack of greenspace, and homes in disrepair [2][3][4]. Children who live in poverty are typically housed in homes that are of lower quality in which they are more likely to be exposed to tobacco smoke, damp conditions, mold, and pests [5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to broad benefits to overall well-being (Engemann et al, 2019), green space is associated with a lower prevalence of smoking (Martin et al, 2020). In places with more green space, children may be exposed to less secondhand and thirdhand smoke (Mahabee-Gittens et al, 2022). Although the exact mechanisms are unclear, a recent study of approximately five million individuals in urban California found that those who lived in closest proximity to existing green space and residential green cover paid an average of $374 less in annual healthcare costs relative to individuals with less access (Van Den Eeden et al, 2022).…”
Section: Outcomes Associated With Developmental Exposurementioning
confidence: 99%